To solve this system of equations, we will use the method of substitution or elimination.
First, let's solve the second equation for x:
-x + 3y = 22
x = 3y + 22
Now, we will substitute x into the first equation:
5(3y + 22) - 4y = -44
15y + 110 - 4y = -44
11y + 110 = -44
11y = -154
y = -14
Now that we have found the value of y, we can substitute it back into the second equation and solve for x:
-x + 3(-14) = 22
-x - 42 = 22
-x = 64
x = -64
Therefore, the solution to the system of equations is x = -64 and y = -14.
solve the system of equations 5x - 4y=-44 -x+3y=22
1 answer